Pemanfaatan Limbah Pertanian Di Indonesia Sebagai Biomaterial Nitroselulosa Untuk Propelan Guna Mendukung Industri Amunisi - Aziz, Sultan; Aritonang, Sovian (Rekayasa Material, Manufaktur dan Energi, 2025)
Propellant production is one of the priority programs in the development of the Indonesia defense industry. One of the main components in double-base propellant is nitrocellulose, which currently relies on imports. With the increasing demand for nitrocellulose, it is crucial for Indonesia to achieve self-sufficiency in its production to support the defense industry. This study aims to identify the potential of agricultural waste as a raw material source for nitrocellulose. The method used is a literature review (meta-analysis) of various references discussing agricultural waste that has the potential to produce nitrocellulose. The results show that several agricultural wastes, such as sago fiber waste, commercial pulp, ramie fiber, Water Hyacinth, and beema bamboo have high cellulose content and potential to be used as raw materials for nitrocellulose. Further research is needed to maximize the nitrocellulose yield from agricultural waste, thus supporting self-sufficiency in propellant production in Indonesia.